A Numerical framework for fatigue lifetime prediction of complex welded structures - Kris Hectors; Wim De Waele; Mia Loccufier; Hans De Backer (Fracture and Structural Integrity)
Ageing infrastructure is of major concern for different industrial sectors across Europe. Fatigue cracking is one of the most important damage mechanisms that affect structural health of welded steel structures. Fatigue assessment of welded details in large, complex structures is a difficult and time consuming task. In this paper a numerical framework for fatigue assessment of welded details is presented. In view of industrial applications, automated hot spot stress algorithms for plate and tubular joints were developed and integrated in the framework. The framework provides practicing engineers with an effective tool for fatigue assessment of different components in conformity with leading design codes. Furthermore, apart from Miner’s rule the framework allows easy implementation of different non-linear damage accumulation models in order to account for load interaction and load sequence effects.